Vision and difference femininity, feminism, and histories of art - Pollock, Griselda (Routledge, 1988)
Griselda Pollock provides concrete historical analyses of key moments in the formation of modern culture to reveal the sexual politics at the heart of modernist art. Crucially, she not only explores a feminist re-reading of the works of canonical male Impressionist and Pre-Raphaelite artists including Edgar Degas and Dante Gabriel Rossetti, but also re-inserts into art history their female contemporaries - women artists such as Berthe Morisot and Mary Cassatt. Pollock discusses the work of women artists such as Mary Kelly and Yve Lomax, highlighting the problems of working in a culture where the feminine is still defined as the object of the male gaze.
Keywords: arts; corps; cours; discipline; europe; femmes* artistes; har4600; har4610; histoire de l'art; histoire et politique; premier cycle; représentation des femme*; régions géographiques; thématiques

The Feminist Critique of Art History - Gouma-Peterson, Thalia; Mathews, Patricia (The Art Bulletin, 1987)
Art criticism and art history from a feminist perspective are recent phenomena, emerging only during the last fifteen years. They have, in their short history, moved from a first generation in which "the condition and experience of being female" was emphasized, to a second generation, beginning in the late 1970s, influenced by feminist criticism in other disciplines and offering a more complex critique of both art and culture through an investigation of the production and evaluation of art and the role of the artist. In this survey, we propose, first, to outline the history of feminist art and art history, then to discuss the interrelated themes in each, and, finally, in the concluding and pivotal sections (IV and V), to discuss various feminist art-critical and art-historical methodologies.
Keywords: 1900-1999; approches et analyses; art moderne; artistes féministes; arts; corps; cours; critique d'art; discipline; discours dominant; femmes* artistes; har4600; histoire de l'art; histoire et politique; maternité; patriarcat; premier cycle; périodes historiques; représentation; sexisme; sexualité; systèmes d'oppressions; thématiques

The Anti-aesthetic: essays on postmodern culture - Foster, Hal (Bay Press, 1983)
For the past thirty years, Hal Foster has pushed the boundaries of cultural criticism, establishing a vantage point from which the seemingly disparate agendas of artists, patrons, and critics have a telling coherence. In The Anti-Aesthetic, preeminent critics such as Jean Baudrillard, Rosalind Krauss, Fredric Jameson, and Edward Said consider the full range of postmodern cultural production, from the writing of John Cage, to Cindy Sherman's film stills, to Barbara Kruger's collages. With a redesigned cover and a new afterword that situates the book in relation to contemporary criticism, The Anti-Aesthetic provides a strong introduction for newcomers and a point of reference for those already engaged in discussions of postmodern art, culture, and criticism. Includes a new afterword by Hal Foster and 12 black and white photographs.
Keywords: 1900-1999; 1950-1959; 1960-1969; 1970-1979; 1980-1989; approches et analyses; arts; corps; cours; discipline; femmes* artistes; har4600; histoire de l'art; postmodernisme; premier cycle; périodes historiques; thématiques

Amantes - Brossard, Nicole (Quinze, 1980)
Ecrire Amantes, pour Nicole Brossard, c'est, nous semble-t-il, tenter de prouver que l'approche du délire est compatible avec l'esprit (cf. p. 13). Dans cette optique, la fiction pratiquée ne peut-être qu'"excès de réalisme". L'oeuvre, comme l'indique l'autrice, ne fait pas de confidences et cependant quelque chose est confié à la compagne-lectrice privilégiée, qui représente le lecteur, sans cesser d'exister. Un lecteur masculin, implicitement exclu, peut-il rendre justice à un tel ouvrage : "entre femmes, la mémoire revient comme une conscience". Il est en tous cas frappé par la façon dont l'abstraction ("excès de réalisme"?) y exerce son pouvoir ("toute vision est en soi mathématique de l'espace"), même si l'autrice multiplie les ancrages dans le réel (banalisé) d'un temps employé, et fait appel à un implicite émotif très fort ("l'expérience infligée au corps des femmes incite à la réalité"). Entre l'essai et le poème, ce texte manifeste une ligne de pensée ferme, l'allusion étant au service exclusif de la thèse. Mais la passion ("de l'intime au politique"), figure centrale de ce livre, fait plus souvent figure de rhétorique, que d'"opéra du dedans." Il s'agit de la poésie de Nicole Brossard, qui s'est imposée comme théoricienne et écrivaine féministe lesbienne et comme figure de proue des écrivain.e.s postmodernistes québécois.e.s. Son travail brouille les frontières entre fiction et théorie, subvertissant les fictions que le discours patriarcal a tissées sur la vie des femmes en travaillant avec les « réalités » de la vie des femmes qui se situent en dehors des codes de la fiction.
Keywords: amériques; approches et analyses; arts; corps; discipline; patriarcat; personnes lesbiennes; poésie; québec; roman; régions géographiques; systèmes d'oppressions; thématiques; écriture des femmes*; émotions; études littéraires